Fatores de virulência e resistência em isolados de Pseudomonas aeruginosa de animais silvestres - Costa, Jackeliny dos Santos (2023)
Pseudomonas aeruginosa is a ubiquitous bacterium, very isolated in nosocomial infections that has an intrinsic resistance to drugs, due to changes in membrane permeability, active efflux of antibiotics, secretion of virulence factors in addition to secretion of β-lactamases enzymes that can be transmitted through of mobile genetic elements such as metallo-beta-lactamase (MBL) IMP, VIM, NDM, SIM, SPM and non-metalogenic β-lactamases such as KPC. Reports of multidrug-resistant (MDR) P. aeruginosa producing MBL carbapenemases and KPC-2 carbapenemase in human and animal isolates are of great concern. The objective of this work was to detect the virulence genes aprA, lasA, lasB, plcH, plcN, toxA and algD, the resistance genes blaIMP-1, blaSPM-1, blaVIM-2, blaNDM-1 and blaKPC-2 and to determine the degree of antimicrobial resistance of Pseudomonas aeruginosa isolates from wild animals treated at the Veterinary Hospital of the Federal University of Mato Grosso. In the 27 isolates tested, the virulence genes were detected: aprA (16/27 - 59.3%), lasA (18/27 - 66.7%), lasB (20/27 - 74.1%), plcH (17/27 - 62.9%), plcN (23/27 - 85.2%) and toxA (21/27 - 77.8%) and the resistance genes: blaVIM-2 (2/27 - 7.4%), blaNDM-1 (5/27 - 18.5%) and blaKPC-2 (11/27 - 40.7%). The antimicrobial resistance rate in the samples was: Cefepime (CPM) 85.2%, Amikacin (AMI) 77.8%, Ciprofloxacin (CIP) 70.4%, Meropenem (MER) 51.8%, Piperacillin/Tazobactam (PPT ) 44.4% and Imipenem (IMP) 29.6%. These data alert to the problem of resistance and contribute to unique health and bring unpublished data such as the detection of blaKPC-2 and blaNDM-1 genes in P. aeruginosa from wild animals in Brazil. The blaKPC-2 gene was more prevalent among carbapenems, raising concern, especially in wild fauna, which has isolates with multidrug resistance, possibly due to genes acquired in an environmental way.